The Refugee Children Legal Rights to Education: The Case of Bambasi Refugee Camp in Ethiopia, Africa (American Journal of Society and Law, 2023)
This study aimed to investigate  the legal rights of refugee children in Bambasi Refugee Camp, Ethiopia. Qualitative method via  case study  were used. There were 11 participants interviewed from the selected officials wring from   teachers, Bambasi Authority for Refugee and Returnees Affairs (ARRA) and Benishangul Gumz Regional State (BGRS) Education Bureau. Some refugees children who  aged  from 12 to 17 years old with their parents authorization were included in the interviews too. They were  chosen based on their academic performance, age and grade level. The whole process were reinforced with field observations and journalling.  Within the periphery of this articulation, results showed that the refugee camp school lack classrooms, library room was not functional and no laboratory rooms as well. The school curriculum need to be revisited as there was no special education in curricular offerings.  Lack of qualified teachers was another issue, language barrier and financial scarcity were among the identified challenges faced by refugee children. Their rights to education need to be protected.  This implied for  the government to look seriously  into the situation of the refugee camp school so refugee children’s right to education will be protected and to reinforce quality  education in the camp.